2016
DOI: 10.1148/radiol.2016151061
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Clinical Predictive Approach and Time Point Analysis of Hepatobiliary Phase Liver Enhancement on Gd-EOB-DTPA–enhanced MR Images: A Multicenter Study

Abstract: Supported by Bayer Yakuhin, Osaka, Japan.q RSNA, 2016 Purpose:To identify biochemical factors associated with liver enhancement over time on gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance (MR) images and predict the optimal time point of the hepatobiliary phase in various clinical settings. Materials and Methods:This study was approved by the institutional review boards, and written informed consent was obtained from the 1903 patients enrolled. Simple a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 27 publications
2
22
1
Order By: Relevance
“…These results suggest that EOB-MRI would be applied for evaluating liver function in the clinical situation. Furthermore, the MRI protocol in the previous studies that evaluated liver function using EOB-MRI did not differ widely from that in our study: the slice thickness was 5.0 mm in the study by Okada et al [ 8 ], 4.0 mm by Nishie et al [ 7 ], and 3.8 mm by Matsushima et al [ 4 ]. Second, in the 3D volumetric analysis, extrahepatic-parenchymal tissues such as portal vein or hepatic vein were included in the whole liver signal intensity calculation: the LSR was the metric primarily used.…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…These results suggest that EOB-MRI would be applied for evaluating liver function in the clinical situation. Furthermore, the MRI protocol in the previous studies that evaluated liver function using EOB-MRI did not differ widely from that in our study: the slice thickness was 5.0 mm in the study by Okada et al [ 8 ], 4.0 mm by Nishie et al [ 7 ], and 3.8 mm by Matsushima et al [ 4 ]. Second, in the 3D volumetric analysis, extrahepatic-parenchymal tissues such as portal vein or hepatic vein were included in the whole liver signal intensity calculation: the LSR was the metric primarily used.…”
Section: Discussioncontrasting
confidence: 45%
“…However, the difference is not assumed to be significant, as the MRI protocols were similar between the two different machines and all images were taken by T-1 weighted technique. In a previous multicenter study, Okada et al reported no significant differences in signal intensity of the liver on EOB-MRI between different MRI scanners [ 8 ]. Fourth, there were a large number of patients excluded for having prior history of portal vein embolization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The additional HP of the gadoxetic acid MRI protocol enables imaging of the liver during a long plateau phase with sufficient hepatocellular uptake for optimal contrast between surrounding parenchyma and malignant lesions. Sufficient uptake is reached as early as 10-20 min after contrast agent injection [20]. Even with standard MRI devices, regardless of the manufacturer, it is possible to achieve good image quality with the very robust 3D T1w fat-saturated breath-hold sequence with a small slice thickness and short breath-hold intervals (approximately 20 s).…”
Section: Discussionmentioning
confidence: 99%
“…15 Furthermore, whether 20 min after Gd-EOB-DTPA administration is the optimal delay to assess liver function remains unclear. Therefore, studies on EOB-MRI have been conducted [16][17][18][19][20][21][22][23][24] using various parameters and indices related to liver enhancement. In this study, liver parenchymal enhancement ratio (LER) is used.…”
Section: Introductionmentioning
confidence: 99%